Incidence, abundance and damage by the sweet potato butterfly (Acraea acerata Hew. and the African sweet potato weevils (Cylas spp.) across an altitude gradient in Kabale district, Uganda - Okonya, J.; Kroschel, Jürgen (2013)
It is increasingly becoming important to understand relationships between temperature (manifested at different altitude levels) and sweet potato insect pest characteristics in light of temperature changes as a result of global warming. Field surveys were conducted in Kabale district of Uganda along an altitude gradient to study the effects of temperature on incidence, abundance and level of damage by main sweet potato insect pests, the sweet potato butterfly (Acraea acerata Hew.) and the African sweet potato weevils (Cylas puncticollis Boheman and Cylas brunneus F.), respectively. A. acerata and Cylas spp. occurred up to an altitude of >2400 m but infestation rate was significantly highest (77% for Cylas spp. and 45% for A. acerata) at low altitudes (1422-1814 m a.s.l.), and lowest (23% for Cylas species and 3% for A. acerata) at altitudes (1992-2438 m a.s.l.). Mean A. acerata density/counts were statistically different across altitudes being highest at the low altitude (4.3 larvae per plant) than at mid and high altitudes. Plant defoliation was highest (3.7%) at low altitude. The highest average number of A. acerata and mean defoliation rates of sweet potato plants recorded in this study was 35 larvae per plant and 27.5% defoliation, respectively. Mean root yield loss by Cylas spp. was significantly higher at low altitude (28.5%) than at mid (6.5%) and high (3.9%) altitudes. All pest damage characteristics significantly decreased with increasing altitude. Insights on the effects of temperature variation on insect pest damage characteristics gained in the present study suggest a possible geographical shift by the pests to higher altitudes due to global warming.